Human Resources Transformation of PT Pelabuhan Indonesia III (Persero) During the Covid-19 Pandemic - Dani Setiawan; Anik Marfistasari (Budapest International Research and Critics University, 2021)
The period of the Covid-19 pandemic is one of the causes of large-scale disruption in the world of human resource management. This disruption leads to employees changing their mindset, attitude, behavior, way of life, way of working and how to use the latest technology. This disruption arises because the speed at which the virus spreads is not comparable with the speed at which companies manage the flexibility of their work systems. Therefore, flexibility is needed in formulating work system adjustments, especially for HRDs in responding to Covid-19. Various challenges that have arisen such as changes in work patterns, digitalization of the economy and changes to the supply chain system have created an urgency for HRD to re-skilling and up-skilling all employees. This research uses qualitative methods, namely descriptive analysis. The process of searching and collecting data is carried out using literature study techniques or literature studies (secondary data). This research has the intention that in its preparation through the process of summarizing various scientific articles from across fields in order to provide a comprehensive review of a phenomenon that is happening.